The power of synergy in discourse: Exploring persuasive language in English mass media - Dmitry S. Khramchenko (Indonesian Journal of Applied Linguistics, 2023)
Contemporary English-language media discourse exerts a powerful influence over public opinion and attitudes, necessitating an exploration into the nuanced mechanisms of persuasive communication. This study examines the concept of synergistic pragmatic effects, focusing on how the combination of diverse language structures influences the efficacy of persuasive verbal interaction. Using a corpus of British and American newspaper articles and opinion essays, this research adopts a robust functional-linguistic approach. It applies both qualitative and quantitative analyses to dissect language techniques such as metaphor, irony, humor, emotionally charged lexemes, hyperbole, interdiscursive references, and rhetorical questions. The findings highlight the transformative power of expertly utilized synergies in achieving communicative goals and refining message interpretation. The interaction of varied language structures provokes particular cognitive and emotional reactions in audiences, shaping their perception of the presented information. This insight is crucial for discourse producers aiming to resonate with their target audience. Additionally, a heightened awareness of these synergies can make recipients less vulnerable to subtle speech manipulation. The practical implications of this research are most salient in the domain of teaching English as a foreign language for cross-cultural professional communication. By melding elements of functional-linguistic analysis, critical thinking, media literacy, and language proficiency, learners can better identify and counteract speech manipulation in media texts. This study augments the current literature on language's role in media communication, underscoring the need for continued research into the interplay between language, discourse, and persuasion in media.